Induction of autotetraploid and morphological, anatomical, and cytological studies of Trichosanthes cucumerina Linn. - Cheng-Li Liu; Heng-Yu Huang; Fu-Rong Xu (BMC Plant Biology)
Abstract Background Polyploidy is a key driver of germplasm innovation in plants, contributing significantly to speciation and the evolution of cultivated crops. Trichosanthes cucumerina Linn. is an economically important crop, valued for its edible, medicinal, and industrial properties. This study aims to explore new germplasm resources of T. cucumerina with desirable traits such as high yield and stress resistance by analyzing and comparing the morphological characteristics, anatomical traits, and root powder microscopic features of diploid and autotetraploid T. cucumerina. Results (1) The most effective method for inducing autotetraploidy was soaking explants in a 0.05% colchicine solution for 72 h, which resulted in the highest explant survival rate (70.67%) and autotetraploid induction rate (31.33%), yielding 145 autotetraploid plants. (2) Flow cytometry and root-tip chromosome counting confirmed that diploid plants had a chromosome number of 2n = 2x = 22, while autotetraploid plants had 2n = 4x = 44. (3) On MS medium supplemented with 6-BA (3.0 mg/L), KT (3.0 mg/L), NAA (1.0 mg/L) and 360.36 mg/L Ca²⁺, autotetraploid stem segments exhibited the highest shoot induction, with a proliferation coefficient of 6.43. (4) The optimal rooting medium for autotetraploid plantlets consisted of MS medium supplemented with 1.0 mg/L NAA, achieving a 100% rooting rate. Following acclimatization and transplantation of regenerated autotetraploid plantlets, the survival rate reached 92%. (5) Compared to diploid plants, autotetraploid plants displayed significantly larger nutritional organs (leaves, stems, roots), enhanced growth parameters (leaf width, stomatal length, stomatal width, root fresh weight, and root dry weight), and more developed cellular structures (palisade tissue, spongy tissue, vascular tissue, starch granules, parenchyma cells, and cork cells). Conclusion This study successfully induced autotetraploidy in T. cucumerina and established an efficient artificial regeneration system. Compared to diploid plants, autotetraploid plants demonstrated significant improvements in morphological characteristics, anatomical traits, and growth parameters. These findings provide valuable resources for breeding new varieties and advancing genetic research on T. cucumerina.